KOMPETISI GULMA DENGAN TANAMAN BUDIDAYA DALAM SISTEM PERTANAMAN MULTIPLE CROPPING - Gayuh Prasetyo Budi (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), 2011)
Multiple cropping is a way of expanding various plants in an area.. This multiple cropping system will give a various agriculture products or various yields, so it can reduce the disadvantageous risk because of the harvest failures in one of the commodity. Besides, the multiple cropping system is based on natural ecosystem where the biodiversity level is higher so it can guarantee the natural equilibrium. One of the obstacles for the farmers in this multiple cropping system is the weed as a growth factor competitor in particular nutrition. It happens especially when the canopy in multiple cropping system does not cover perfectly, so that the weeds problem can be more complex. To reduce the disadvantages are to give the nutrition in an exact dosage, to choose the various plants which can make canopy fast, to arrange the planting distance exactly and multiple cropping system with legume. Keywords: weed competition, plant, multiple cropping.